Preferential adsorption of nitrate with different trialkylamine modified resins and their preliminary investigation for advanced treatment of municipal wastewater. (May 2019) - Li, Qimeng; Lu, Xiaoyun; Shuang, Chendong; Qi, Chengdou; Wang, Guoxiang; Li, Aimin; Song, Haiou
Abstract: In this paper, a series of mono-functional and bifunctional anion exchange resins with different kinds of trialkylammonium groups were synthesized and used for adsorption of nitrate from aqueous solution. The obtained resins were systematically characterized by scanning electron microscopy, Fourier transform infrared spectrometry and pore size distribution. Adsorptive behaviors and mechanisms were investigated by batch experiments. The nitrate could be preferentially adsorbed in the presence of chloride, sulfate and humic acid by longer-chain trialkylamine modified resins. Especially, the L20 resin with the triethylammonium functional group was demonstrated to possess high selectivity toward nitrate with the highest distribution coefficient among all tested resins. For both single and bi-solutes systems, the adsorption isotherm data could be well fitted with the Langmuir model, while the experimental kinetic data was well described by both pseudo first-order and second-order kinetic model. The L20 resin could be reused after many adsorption-desorption cycles with most of its virgin adsorption capacity for advanced wastewater treatment, indicating its great potential for the selective and efficient removal of nitrate from large amounts of municipal wastewater or surface water. Graphical abstract: Image 1 Highlights: The anion-exchange resins with different trialkylammonium groups were prepared. The NO3 − could be preferentially adsorbed with the co-existence of Cl − or SO4 2− . The synthetic resins exhibited superior anti-fouling performance for humic acid. Effective reuse of synthetic resins was achieved by chemical regeneration. The application of resins in a fluidized bed greatly extended the working lifetime.